Symptomatic hemodialysis arteriovenous fistula with associated subclavian stenosis and a normal fistulogram - Yudhvir Bhatti, BSc; Kiat Tsong Tan, MBChB, MD, MRCP, FRCR, FRCPC (Radiology Case Reports, 2024)
While arteriovenous fistulas (AVFs) are the optimal route of access for hemodialysis in terms of duration of patency and infection rates, they can still fail due a variety of reasons. Most commonly, AVF failure is due to venous stenotic lesions, resulting in reduced blood flow rate across the fistula. Fistulograms are often used to investigate cases of symptomatic or poor fistula function. This case discusses a 71-year-old man with a mature brachiocephalic AVF who presented with severe right upper extremity edema, and had a negative fistulogram, despite a severe stenosis in his AVF.